The acquisition of the English inflectional -s morphemes by young L1 Chinese speakers - Chan, Swee Heng; Wong, Bee Eng; Teo, Pauline Hwa Ling (Penerbit Universiti Kebangsaan Malaysia, 2004)
This paper examines the acquisition of the inflectional –s morphemes (the plural marker, genitive marker and third person singular present tense marker) in English by eighteen young ESL learners from two Chinese primary schools. Learners were shown pictures as stimuli, and they were asked to describe the pictures in English. During these sessions, the descriptions by the learners and the conversations between the researcher and the learners were taped and later transcribed. The results of the study indicated that learners exhibited a distinct accuracy order for the morphemes. The learners also exhibited variability and produced overgeneralizations in their L2 utterances. The findings in fact suggested that the acquisition of the –s morpheme was systematic and staged. A discussion on the reasons for the phenomenon then followed and some implications were drawn for the teaching of these forms to young L1 Chinese speakers of L2 English.